2022
DOI: 10.1098/rsbl.2022.0167
|View full text |Cite
|
Sign up to set email alerts
|

Skin bacterial microbiome diversity predicts lower activity levels in female, but not male, guppies,Poecilia reticulata

Abstract: While the link between the gut microbiome and host behaviour is well established, how the microbiomes of other organs correlate with behaviour remains unclear. Additionally, behaviour–microbiome correlations are likely sex-specific because of sex differences in behaviour and physiology, but this is rarely tested. Here, we tested whether the skin microbiome of the Trinidadian guppy, Poecilia reticulata , predicts fish activity level and shoaling tendency in a sex-specific manner. High-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 79 publications
2
5
0
Order By: Relevance
“…Alpha diversity was negatively correlated with both behaviours; sh with higher Chao1 and Faith_pd diversities displayed lower levels of activity and inspection. These results mirror the decline in activity with increasing Faith_pd skin diversity previously observed in female guppies [14]. Dysbiosis due to infection, hormonal production or olfactory regulation were proposed to explain the correlation in the case of the guppies, but whether there is a causal relationship and its possible direction was unclear [14].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Alpha diversity was negatively correlated with both behaviours; sh with higher Chao1 and Faith_pd diversities displayed lower levels of activity and inspection. These results mirror the decline in activity with increasing Faith_pd skin diversity previously observed in female guppies [14]. Dysbiosis due to infection, hormonal production or olfactory regulation were proposed to explain the correlation in the case of the guppies, but whether there is a causal relationship and its possible direction was unclear [14].…”
Section: Discussionsupporting
confidence: 61%
“…Germ-free zebra sh and larvae supplemented with the probiotic Lactobacillus plantarum display less anxiety-related behaviours compared to controls raised under standard conditions, supporting the suggestion that the microbiome plays a role in regulating the stress response in this sh [13]. Skin microbiota also seems to in uence activity levels in sh in a sex-speci c manner, as a recent study in guppies indicated [14]. The association between microbiome and behaviour can be particularly important given the negative effects of stress observed in the sh skin and gut microbiomes [15].…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, studies on several other vertebrates found no evidence for biological sex to be a significant variable shaping skin microbial communities 6 8 . Recent studies have explored the relationship between fish biological sex and skin microbiome 9 11 . For instance, female guppies found to have a higher abundance of certain bacterial taxa, such as Flavobacterium, compared to males 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have explored the relationship between fish biological sex and skin microbiome 9 11 . For instance, female guppies found to have a higher abundance of certain bacterial taxa, such as Flavobacterium, compared to males 9 . These differences are thought to be driven by differences in hormonal profiles and immune function between the sexes.…”
Section: Introductionmentioning
confidence: 99%